PENTINGNYA PENERAPAN CALESTIAL MANAGEMENT BAGI SUMBER DAYA MANUSIA DI BANK PEMBIAYAAN RAKYAT SYARIAH - Trimulato Trimulato (Universitas Negeri Surabaya, 2017)
Shari'ah Banking now has a strong legal law with the presence of the law number 21 of 2008 on banking Shari'ah. It is very influential the existence and sought by many. Development of shariah banking must be matched with adequate resources and qualified. Labor in BPR shariah continued to increase, from December 2014 to December 2015 grew to 7.525%. Not only the quantity but the quality should also be considered, it takes a celestial concept should be applied for the Management of human resources in shariah banking. Paper uses a descriptive qualitative, necessary to apply celestial management for human resources in BPR shariah. The results of paper the human resources in BPR shariah growth, then the need for the application of celestial management for human resources in Islamic banks to create good quality. The shariah banking is an institution whose business inseparable from the rule of religion or spiritual aspect.